Dairy Manure Digestate Age Increases Ultrasound Disintegration Efficiency at Low Specific Energies - Matthijs H. Somers; Samet Azman; Ruud Vanhecke; Lise Appels (Energies, 2021)
Substantial insight into the effect of ultrasound disintegration on the changes in biochemical parameters of manure digestate and digestate age is needed to understand the potential of digestate treatment. To address this knowledge gap, in this study, the effect of digestate age on the efficiency of ultrasound (US) disintegration was investigated. In this scope, dairy manure digestate samples were incubated in an oven at 37 °C for a predetermined amount of time to obtain simulated digestate ages of 15, 22, 29, 36 and 43 days. The results showed that US disintegration efficiency significantly affected the initial biochemical characteristics of digestate and that the digestate age had a significant effect on the US disintegration efficiency. This effect diminished when the applied specific energy (SE) was higher than 3000 kJ/kg total solids (TS). A numerical partial least squares (PLS) model was constructed to investigate the relative influences of the initial biochemical parameters on the soluble chemical oxygen demand (sCOD) and soluble carbohydrates (sCARB) solubilization. The results of the high-quality (R2 = 0.8) model indicated that the most influential parameters for the efficiency of US disintegration were the SE, the initial sCARB0, the TS, the initial sCOD0 and the volatile solids (VS).